Course of Sars-CoV2 Infection in Patients with Cancer Treated with anti-PD-1: A Case Presentation and Review of the Literature. (2nd February 2021) - Pala, Laura; Conforti, Fabio; Cocorocchio, Emilia; Ferrucci, Pierfrancesco; De Pas, Martino Tommaso; Stucchi, Sara; Repetto, Matteo; Saponara, Maristella; Queirolo, Paola
Abstract: The outbreak of COVID-19 pandemia is a major health worldwide concern. Patients with cancer might have a worse outcome, because of the immunosuppression determined by the tumor itself and anti-cancer treatments, including chemotherapy and radiotherapy. The impact and course of viral infection in patients receiving immunotherapy remains unknown. We report the case of a patient with metastatic melanoma, long responder to anti PD-1 blockade who got infected with Sars CoV-2, recovering without sequelae. A critical review of literature was performed. Limited data available in literature support the possibility to continue the immunotherapy in patients with cancer under control.